Tamil Weekends: Intergenerational Perspectives on Belonging - Perera, Niru (Palgrave Pivot, 2020)
“Tamil weekends” describe how second-generation migrants are involved in an intensively packed mix of Tamil linguistic, cultural and religious activities, mostly on the weekends, as part of the first generation’s to (re)create home. Drawing from an ethnographic study in a Tamil Hindu temple, this chapter explores how adolescent students perceive the transmission efforts of the first generation, and what it means for their sense of belonging and their sense of Tamilness in the homeland of Sri Lanka and the new home of Australia. I highlight how first- and second-generation ideologies regarding Tamil identity and belonging are changing with time, largely due to new interpretations of “being Tamil” that vary between and within generations. At the same time, as a result of the threat to Tamil culture in Sri Lanka, there is an enduring sense of duty to maintain the language, religion and culture outside of the homeland.